Regional or national poverty lines? The case of Uganda in the 1990s - Simon Appleton (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Absolute poverty lines are often derived from the cost of obtaining sufficient calories. Where staples vary across regions, such poverty lines may differ depending on whether they are set using national or regional food baskets. Regional poverty lines are open to the objection that they may be contaminated by income effects. This paper explores this issue by focussing on Uganda, a country where widening spatial inequalities in the 1990s have caused concern. Conflicting results from earlier studies have suggested that the spatial pattern of poverty in Uganda is very sensitive to whether national or regional food baskets are used in setting poverty lines. We confirm this suggestion by comparing the spatial profile of poverty in 1993 using national and regional poverty lines. However, since the regions consuming the more expensive staple sources of calories are also those with higher incomes, using simple regional poverty lines is problematic. Instead, a method of setting regional poverty lines is considered that adjusts for income differentials between regions. Even with this adjustment, the use of regional food baskets implies a markedly different.
Keywords: I32; O15; 330; Uganda; poverty; inequality; Armut; Uganda